1978
DOI: 10.1002/pol.1978.180160113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen bonding and ionic aggregation on the melt rheology of an ethylene–methacrylic acid copolymer and its sodium salt

Abstract: A study has been made of the dynamic and steady shear melt rheology of an ethylene-methacrylic acid copolymer, its methyl ester, and 70% neutralized sodium salt. Measurements were made with a Rheometrics mechanical spectrometer using the eccentric rotating disks and cone-and-plate geometries over a temperature range of 120-180°C and a frequency range of 10-3 to 102 rad/sec. Correspondence was found between steady shear viscosity and the complex dynamic viscosity for the ester and acid materials. Over the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 25 publications
(8 reference statements)
5
45
2
Order By: Relevance
“…The diminution of MI values of copolymers of S and MA and their salts containing primarily sodium and potassium ions was observed earlier15–17, but there were no measurements of MI of S and AA copolymers and of the ionomers obtained.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The diminution of MI values of copolymers of S and MA and their salts containing primarily sodium and potassium ions was observed earlier15–17, but there were no measurements of MI of S and AA copolymers and of the ionomers obtained.…”
Section: Resultsmentioning
confidence: 80%
“…The documented rheological studies of ionomers based on ethylene,16 propylene,17 and styrene18, 19 also indicated an enhancement of melt viscosity and activation energy of viscous flow of these ionomers with an increase in the content of salt. These observations are a consequence of intermolecular interactions between salt groups for the metal salt derivatives.…”
Section: Introductionmentioning
confidence: 94%
“…A small number of studies have reported steady shear behavior of ionomers, including studies with polymer backbones based on polyethylene, 14,18,19 polypropylene, 20 poly(styrene-co-ran-butyl methacrylate), 21 polyester, 22,23 and polystyrene. 24−29 Nonlinear extensional flows have also been used to characterize the rheological behavior of ionomers, but that literature is very limited.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly to peroxide cured polymers, which experience an increase in viscosity and modulus owing to the formation of chemical cross‐links, the addition of ionic functionality to non‐polar polymers alters their melt rheology because of the network effects of ion‐pair aggregation . This enables us to monitor the kinetics of the reaction through simple time sweep experiments, which record the evolution of the LVE functions of the polymer as a function of time.…”
Section: Resultsmentioning
confidence: 99%